A quest for an integrated management system of children following a drowning incident: A review of the literature - Rossouw, S.; Maree, C.; Latour, Jos (2023)
Purpose: Management of children following a drowning incident is based on specific interventions which are used in the prehospital environment, the emergency department (ED) and the Paediatric Intensive Care Unit (PICU). This paper presents a review of the literature to map and describe the management and interventions used by healthcare professionals when managing a child following a drowning incident. Of specific interest was to map, synthesise and describe the management and interventions according to the different clinical domains or practice areas of healthcare professionals. Design and Methods: A traditional review of the literature was performed to appraise, map and describe information from 32 relevant articles. Four electronic databases were searched using search strings and the Boolean operators AND as well as OR. The included articles were all published in English between 2010 and 2022, as it comprised a timeline including current guidelines and practices necessary to describe management and interventions. Results: Concepts and phrases from the literature were used as headings to form a picture or overview of the interventions used for managing a child following a drowning incident. Information extracted from the literature was mapped under management and interventions for prehospital, the ED and the PICU and a figure was constructed to display the findings. It was evident from the literature that management and interventions are well researched, evidence-informed and discussed, but no clear arguments or examples could be found to link the interventions for integrated management from the scene of drowning through to the PICU. Cooling and/or rewarming techniques and approaches and termination of resuscitation were found to be discussed as interventions, but no evidence of integration from prehospital to the ED and beyond was found. The review also highlighted the absence of parental involvement in the management of children following a drowning incident. Practice Implications: Mapping the literature enables visualisation of management and interventions used for children following a drowning incident. Integration of these interventions can collaboratively be done by involving the healthcare practitioners to form a link or chain for integrated management from the scene of drowning through to the PICU.